2021
DOI: 10.22207/jpam.15.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Biomedical Potentialities of Terpenoids – A Review

Abstract: Terpenoids are the most diverse and largest class of chemicals of the innumerable plant-based compounds. Plants carry out a number of essential growth and production functions using terpenoid metabolites. In contrast, most terpenoids are used in the abiotic and biotic systems for complex chemical interactions and defense. Terpenoids derived from plants mostly used humans for pharmaceutical, food, and chemical industries in the past. However, recently biofuel products have been developed by terpenoids. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Terpenoids and sesquiterpenes are among the main categories of metabolites found in viscum samples. Extensive studies report their antimicrobial, antioxidant, anticonvulsive, analgesic, neuroprotective, anti-inflammatory, anti-allergic, and antitumoral activities [ 51 , 60 , 65 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Terpenoids and sesquiterpenes are among the main categories of metabolites found in viscum samples. Extensive studies report their antimicrobial, antioxidant, anticonvulsive, analgesic, neuroprotective, anti-inflammatory, anti-allergic, and antitumoral activities [ 51 , 60 , 65 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“… 15 In a surge of new therapies from natural sources, terpenoids are found to be effective against NAFLD in several animal models. 16 , 17 This study aimed to assess the anti-NAFLD effect of safranal at two dosing levels in a rat model of HFD. To the best of our knowledge, this is the first study reported by safranal in which we investigated its effect on hepatic lipid accumulation induced by prolonged consumption of a purpose-built diet, as well as its impact on subsequent pathology associated with steatosis, characterized by NASH and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Furthermore, terpenoids have been identified as antioxidant, anti-inflammatory, anti-hyperglycemic, anti-cancer, and immunomodulatory chemical compounds and have been shown to exhibit anti-fatty liver activities. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…The capitula of tea Chrysanthemum cultivars possess medicinal and economic value rather than aesthetic characteristics. The flowerheads of tea Chrysanthemum mainly produce and emit 3-carene, camphene, eucalyptol, camphor, 2-bornanone and β-selinene, which have the functions of expelling wind and heat, easing anxiety and improving eyesight [ 47 ]. These terpenoids are mainly stored in the glandular trichomes, indicating that the production of volatile terpenes could be increased by increasing the density of glandular trichomes.…”
Section: Discussionmentioning
confidence: 99%